Differences in mitochondrial function between brain and heart of senile rats exposed to acute hypobaric hypoxia: Role of nitric oxide - La Padula, P. (2023)
Rat brain and heart display different endogenous protective responses against hypobaric hypoxia in an age-dependent way. The aim of the present work was to evaluate the effects of acute hypobaric hypoxia (HH, 48 h) on brain and heart mitochondrial function as well as the participation of nitric oxide (NO) in old rats (22-month old). Cortical mitochondria from rats exposed to HH decreased respiratory rates (37 %, state 3) and membrane potential (20 %), but NO and H2O2 production increased by 48 %, and 23 %, respectively. Hippocampal mitochondria preserved O2 consumption and H2O2 production, decreased membrane potential (18 %) and increased NO production (46 %). By contrast, HH decreased NO production (53 %) in mitochondria from left heart ventricles associated with increased cytochrome oxidase activity (39 %) and decreased NADPH oxidase activity (31 %). Also, a tendency to increase complex I-III (24 %) and complex II-III (65 %) activity was observed. In conclusion, after HH hippocampal and cortical mitochondria showed mild uncoupling and increased NO production. However, only the hippocampus preserved O2 consumption and H2O2 levels. Interestingly, heart mitochondria showed a decreased ROS production through increased cytochrome oxidase activity associated with a decrease in NO production. This may be interpreted as a self-protective mechanism against hypoxia.